Platinum(IV) Prodrugs Conjugated to DSPE-PEG for Development of Iron Oxide Nanoparticle Micelles for Multimodal Cancer Therapy - Dom Conway (2024)
Platinum chemotherapy drugs are commonly used in cancer treatment, but they are limited by the side effects and mechanism used for inducing cell death. The work presented here pursues a new approach and nanoparticle-based platform for using these chemotherapy agents more effectively. The inert nature of platinum(IV) complexes is combined with intrinsically therapeutic iron and lipid loaded nanoparticles to provide a strategy to deliver them to the cancer cells and trigger complementary or even synergistic therapeutic effects with lower collateral damage to healthy cells. A multistep synthesis procedure was devised to enable the ligands added to form the platinum(IV) complex to be used to create different types of nanoparticle constructs and to attach other useful ligands and molecules that can be used to target and enhance cancer cell death in different ways (i.e. triggering apoptosis and ferroptosis). The platinum(II) complexes used in this study are octahedral platinum(IV) prodrugs of square-planar cis-diamino-dichloro platinum(II) (cisplatin) and diamino-cyclohexane-oxalato platinum(II) (oxaliplatin). These prodrugs were synthesised by oxidation reactions of the platinum(II) complexes by hydrogen peroxide and adding differing ratios of hydroxyl and acetyl ligands to the compound’s free axial sites in different solvent conditions, either water or glacial acetic acid. Then further reacting of these compounds with succinic anhydride generated acetyl-succinate or bis-succinate platinum(IV) compounds. These platinum(IV) compounds were then conjugated to a 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)] (DSPE-PEG-amine [2000]) phospholipid (PL) using a dicyclohexylcarbodiimide (DCC)-mediated conjugation reaction to form DSPE-PEG-Pt(IV) derivatives. The biocompatible DSPE-PEG was chosen due to its amphiphilic nature, to provide water solubility and due to PEGylation’s known ability to enhance circulation time by evading the non-specific binding of plasma proteins. In the formation of micelles, the DSPE-PEG-Pt(IV) hydrocarbon chain was then used to promote a self-assembly process with oleic acid-coated iron oxide nanoparticles (IONPs) driven by hydrophobic interactions and van der Waals forces. The IONPs used can help initiate ferroptosis; which is a type of non-apoptotic, iron dependant form of programmed cell death discovered recently. Ferroptosis is activated by lipid peroxide radicals being formed with iron as the catalyst, this leads to specific morphological changes that lead to cell death. Cancer cells have a greater uptake of iron than healthy cells and export iron less effectively; this hoarding of iron can be used to target and kill cancer cells, especially when the cancer cells have developed resistance to other forms cell death. Four platinum(IV) asymmetric and symmetric succinate compounds were synthesised, one asymmetric and one symmetric prodrug analogue of both cisplatin and oxaliplatin. These four compounds were then functionalised with DSPE-PEG, and the DSPE-PEGylated Pt(IV) complexes were successfully utilized to form micelles filled with IONPs as the core.